Methodological exemplar of integrating quantitative and qualitative evidence – supportive care for men with prostate cancer: what are the most important components?. (24th August 2016) - Huntley, Alyson L.; King, Anna J.L.; Moore, Theresa H.M.; Paterson, Charlotte; Persad, Raj; Sharp, Debbie; Evans, Maggie
Abstract: Aims: To present a methodological exemplar of integrating findings from a quantitative and qualitative review on the same topic to provide insight into components of care that contribute to supportive care that is acceptable to men with prostate cancer. Background: Men with prostate cancer are likely to live a long time with the disease, experience side effects from treatment and therefore have ongoing supportive care needs. Quantitative and qualitative reviews have been published but the findings have yet to be integrated. Design: Integration of quantitative and qualitative synthesized evidence. Data source: Two previously published systematic reviews. Review methods: Synthesized evidence on supportive care for men with prostate cancer was integrated from two previously published systematic reviews: a narrative quantitative review and a qualitative review with thematic synthesis. These two streams of synthesized evidence were synthesized using concurrent narrative summary. Data from both reviews were used to develop a set of propositions from which a summary of components of care that likely to contribute to supportive care acceptable to men with prostate cancer were identified. Results: Nine propositions were developed which covered men's supportive care focusing on the role of health professionals. These propositions were used to compose nine components of care likely to lead to supportive care that is acceptable to men with prostate cancer. Some of these components are no/low cost such as developing a more empathic personalized approach, but more specific approaches need further investigation in randomized controlled trials, for example, online support. Conclusion: This methodological exemplar demonstrates the integration of quantitative and qualitative synthesized data to determine components of care likely to lead to provision of supportive care acceptable to men with prostate cancer.